Gamification: A resource for motivation and fidelization at museums - Novillo López, Miguel Ángel; Costa Román, Óscar; Barrientos Fernández, Amelia; Pericacho Gómez, Francisco Javier; Arigita García, Amaya; Sánchez Cabrero, Roberto (Clio. History and History Teaching, 2018)
Gamification, understood as the application of the philosophy of game to non-play contexts, is experiencing a spectacular development in areas of diverse nature in recent years. While it is more commonly accepted that the main functions of museums are to preserve and make their own collections public, it is essential for them to be able to connect successfully with users using innovative and accessible means and strategies. In the following pages we will show how gamification is an ideal resource to motivate, retain and influence user behaviour.
Keywords: Gamification; museums; users; motivation; fidelization; strategies